Among Independence, Sovereignty and Autonomy: The Dutch Caribbean - Mine Kojima (Études Caribéennes)
This paper critiques the structure and functionality of the 21st century nation-state through analysis of emancipatory decisions in the former Dutch Caribbean colonies of Aruba, Curaçao, and Suriname.Suriname, the most culturally Dutch of the Caribbean territories, was the first of the former colonies to secede from the Netherlands. Although Suriname achieved independence in 1975, the economy remained heavily reliant on the policies of the United States. As such, the Surinamese government prioritized the interests of NATO and struggled to reconfigure its preexisting relationship with the suzerain. This dynamic strained Surinamese relation with Latin American nations more actively resisting US imperialism and isolated Suriname politically.Aruba became a constituent country in 1986; however, this shift was not contemporaneously reflected in Curaçao. Curaçao had headed the former Colony of Curaçao and Dependencies, and independence would have weakened its influence on the other islands whose governing structure would have remained unchanged. While Aruba had the opportunity to claim equal status with Curaçao, it instead pursued emancipation. Demographically Mestizo unlike neighboring islands, Aruba was eager to distinguish itself from Curaçao, where advocacy for decolonization arose with support from regional Black Power movements. Aruba and Curaçao had a long history of human exchange with Latin American continent from the pre-Columbian period. The inhabitants, especially those of African descent excluded from citizenship on the basis of race, moved to Spanish colonies where citizenship was granted upon conversion to Roman Catholicism. The people could use religion to obtain citizenship. They had no loyalty to the European empire nor a sense of belonging to any European kingdom. What they wanted was citizenship and human rights.Around the time Suriname declared independence, European governments began to promote neo-liberal policies that advanced smaller or limited government function. The former Dutch empire was itself abandoning its role as sovereign of a nation-state. Aruba, which had witnessed Suriname’s predicament post-independence and where sense of belonging within the nation-state was historically weak, finally elected to retain within the Dutch Kingdom. To become an independent nation would have entailed severing preexisting ties with Europe and rendered the territory more vulnerable, since globalization often facilitates interference from supranational institutions and military alliances such as the EU and NATO. The trajectory of Aruba prompts questions regarding the true definition and function of the 21st century nation-state.Today, even independent nations comply with international regulations and belong to multinational free trade spheres and military alliances. Due to Dutch disinterest, Aruba and Curaçao enjoyed a greater degree of autonomy. Thus, dependent territories such as Aruba that are capable of maintaining intercontinental and supranational affiliations do not immediately necessitate full independence